PENENTUAN KOMODITAS UNGGULAN TANAMAN PANGAN DI KABUPATEN SUMBAWA BARAT - Muhammad Nursan (Universitas Teuku Umar, 2017)
West Sumbawa regency is one of the regency in Indonesia where the food crops sub-sector is the main livelihood of the community. In the framework of increasing the competitiveness of the region and increasing the production of food crops, the development of food crop commodities should be determined based on the region's superior commodities. This study aim to (1) determine the commodity of food crop base, (2) determine the commodity of food crop. This research was conducted in West Sumbawa Regency. The data used in this study is cross section data were obtained from expert teams. The collected data were analyzed using Location Quotient (LQ), and Analytic Hierarchy Process (AHP) analysis method. The results showed that the commodity of food crop base in West Sumbawa Regency consisted of paddy which is the base commodity in 6 sub-districts, sweet potato and peanut is the base commodity in 4 districts, soybean is the base commodity in 5 districts, cassava and green beans are commodities Base on 3 sub-districts, and corn is a base commodity in 2 subdistricts. Superior commodity of food crops that become priority in West Sumbawa Regency is paddy is commodity with first priority with value 0,288, corn (0,285), soybean (0,158), green beans (0,150) and peanut (0,119).